Alexithymia, Emotional Distress, and Perceived Quality of Life in Patients With Hashimoto’s Thyroiditis - Martino, Gabriella; Caputo, Andrea; Vicario, Carmelo M.; Feldt-Rasmussen, Ulla; Watt, Torquil; Quattropani, Maria C.; Benvenga, Salvatore; Vita, Roberto (Frontiers in Psychology, 2021)
Emotion-processing impairment represents a risk factor for the development of somatic illness, affecting negatively both health-related quality of life (HRQoL) and disease management in several chronic diseases. The present pilot study aims at: i) investigating the associations between alexithymia and depression, anxiety, and HRQoL in patients with Hashimoto's thyroiditis (HT); ii) examining the association between these three psychological conditions together with HRQoL, and thyroid autoantibodies status as well as thyroid echotexture in patients with HT; iii) comparing the intensity of all these clinical psychological features in patients with HT versus controls. Twenty-one patients with serologically or ultrasonographically verified HT and sixteen controls with non-toxic goiter or post-surgical hypothyroidism were recruited for this study. Serum thyrotropin [TSH] and free thyroxine [FT4] as well as thyroid autoantibodies (thyroglobulin antibodies [TgAb] and thyroid peroxidase antibodies [TPOAb]) were assayed. Alexithymia, depression, anxiety and HRQoL were assessed with Toronto Alexithymia Scale (TAS-20), Beck Depression Inventory-second edition (BDI-II), Hamilton Anxiety Rating Scale (HAM-A) and Health Survey Short Form-36 (SF-36), respectively. A negative relationship between the difficulty to describe feelings and the cognitive component of depression was found (r = -.46, p = .04). Besides, patients with seronegative HT had lower somatic anxiety than patients with HT who tested positive (respectively, r = -.68, p = .01 and r = -.59, p = .04). Besides, no statistically significant difference was found between patients with HT and controls with regard to somatic anxiety. The present study suggests the relevance of alexithymia in patients suffering from HT, which may be intertwined with a possible state of underreported depression that is mainly expressed through physical complaints. Promoting the capability to describe and communicate feelings could contribute to psychological elaboration and coping with the disease and, consequently, to the improvement of self-management and perceived HRQoL.